ETNOGENEZA SŁOWIAN W POLSKICH KRONIKA CH ŚREDNIOWIECZNYCH - Grzesik, Ryszard (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
Historiography including the story of native origins created ideological bonds in new states, created the state and afterwards national consciousness. The Latin cultural roots of Christianity and the awareness of the similarities of Slavic languages played a role in ethnographical stories told in Polish medieval chronicles. While keen on presenting Polish origins, the first Polish chronicles did not deal with ethnogenesis of Slavs. Only in the 14th century did the chroniclers adopt an ethnogenetical approach. Dzierzwa introduced the Biblical genealogy to Polish medieval historiography and derived the origins of the Poles from Japhet. The Slavic Interpolator of the Great-Polish Chronicle presented the Pannonian concept of the origin of Slavs which probably emerged in Great-Moravia and was preserved in Rus’ historical tradition. This story was used by John Dąbrówka in his commentaries to the Chronicle of Vincent Kadłubek and by John Długosz who created the erudite vision of Polish ethnogenesis, based on popular tables of nations.